Risk Management Perspective for Evaluating Community Development Programs - Pranoto Effendi (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2024)
Community development programs are very important in reducing poverty and enhancing societal prosperity by improving quality of life, fostering economic empowerment, and promoting inclusivity. However, not all the programs have success as expected. This study examines ten evaluation studies of community development programs across various areas and tries to find common weaknesses. A qualitative analysis of evaluation studies identifies shortcomings in three domains i.e. program design and management, stakeholder engagement and participation, and external resource constraints. It is argued that these shortcomings are largely predictable and highlight the need for proactive strategies. The paper suggests that embedding risk management into the conception and implementation of community development programs can mitigate these challenges. A simplified framework adapted from project management practices is proposed, encompassing risk identification, measurement, assessment, evaluation, and control. By systematically integrating risk management, community programs can anticipate obstacles, strengthen accountability, and enhance their likelihood of success. Recommendations include applying risk management throughout program cycles and conducting post-implementation evaluations to inform future initiatives.